Familiarisation et dé-familiarisation : la figure de l’« étranger » dans la comédie indo-britannique - Amandine Ducray (Revue LISA)
Though considered as a popular form of light entertainment, could not comedyalso be a means of “correcting customs by laughing at them” (castigat ridendomores)? This article, which focuses on three British-Asian comedies – East is East (Damien O’Donnell, 1999; screenplay by Ayub Khan Din), Bend It Like Beckham (Gurinder Chadha, 2002) and Bride and Prejudice (Gurinder Chadha, 2004) – aims, through a comparative analysis, at highlighting common discursive and iconographic trategies. Meant to make the audience laugh, these films nevertheless try to changeboth the representation and perception of British-Asian ethnic minorities as well as hose of so-called “indigenous” Britons themselves. By giving an ethnic dimension to he notions of “familiarisation” and “de-familiarisation” – essential to comedy at large– the three directors thus seem to have encouraged the emergence of mainstream BritishAsian cinema in Britain, whilst celebrating, through comedy, some fusion of identitiesbetween the “Other” and the “Self”.